Understanding academic literacy facilitators’ perceptions of ChatGPT through framing theory - Brokensha, S.; Brooks, M. (South African Journal of Higher Education, 2025)
Currently, ChatGPT (Generative Pre-training Transformer) causes disruption in sectors that run the gamut from retail and marketing to journalism and healthcare. This chatbot also affects higher education, with scholars either extolling its potential or accentuating its pitfalls. Advantages of early adoption of ChatGPT include fostering students’ self-directed learning and developing their research skills, while disadvantages mainly reflect educators’ concerns that it may harm the integrity of online examinations and make it difficult, if not impossible, to detect plagiarism. To determine educators’ perceptions with respect to the nature and application of ChatGPT in the context of students’ academic writing, this study conducted focus-group discussions with academic literacy facilitators from a South African tertiary institution. Working within a qualitative research paradigm and employing thematic analysis as a broad methodological approach, discussions were analysed using framing theory. The latter is a sociological concept based on the notion that a phenomenon exhibits myriad values, given that it is perceived through different frames that, in turn, impact the choices people make about that phenomenon. Understanding how educators perceive the nature of ChatGPT and to what extent they accept it paves the way towards challenging unrealistic expectations about ChatGPT’s human-like capabilities and addressing the ethical concerns that educators may have about its deployment in the writing classroom.